2021
DOI: 10.1071/fp20303
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic memory and growth responses of the clonal plant

Abstract: The responses of plants to recurrent stress may differ from their responses to a single stress event. In this study, we investigated whether clonal plants can remember past environments. Parental ramets of Glechoma longituba (Nakai) Kuprian were exposed to UV-B stress treatments either once or repeatedly (20 and 40 repetitions). Differences in DNA methylation levels and growth parameters among parents, offspring ramets and genets were analysed. Our results showed that UV-B stress reduced the DNA methylation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…These results support the first hypothesis that parental effects could impact offspring growth of different vegetative generations of clonal plants. Similarly, previous studies have shown that parental environment effects can persist across vegetative generations in clonal plants (e.g., González et al, 2017;Dong et al, 2018b;Portela et al, 2020;Zhang et al, 2021). Our results suggest that paternal effects are fast in clonal plants as the vegetative reproduction is rapid.…”
Section: Discussionsupporting
confidence: 87%
“…These results support the first hypothesis that parental effects could impact offspring growth of different vegetative generations of clonal plants. Similarly, previous studies have shown that parental environment effects can persist across vegetative generations in clonal plants (e.g., González et al, 2017;Dong et al, 2018b;Portela et al, 2020;Zhang et al, 2021). Our results suggest that paternal effects are fast in clonal plants as the vegetative reproduction is rapid.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, shaded parents of P. persicaria produced offspring with increased fitness in shade as well as a greater competitive impact on plant neighbours (Baker et al 2019). Our previous study also suggested that the parental ramets of clonal G. longituba could record their UV-B radiation experience and form epigenetic memory via a decrease in DNA methylation levels, the growth of offspring and genets was clearly affected by parental experience (Zhang et al 2021).…”
Section: Role Of Parental Epigenetic Memory In the Habitat Selection ...mentioning
confidence: 63%
“…At the end of the experiment, the biomass of parental ramets was improved by low UV-B radiation (5 μW cm −2 ), which was related to the eustress effects of low-dose UV-B stress. Eustress is an activating, stimulating stress that is a positive element in plant development; when a plant experiences eustress, its metabolism is adjusted, and the plant acclimates to the new environment (Zhang et al 2021); thus, the parental biomass was increased by this mild, elastic UV-B radiation. Furthermore, although only parental ramets were exposed to UV-B radiation, the growth of the parent as well as the genets was influenced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations